Managerial strategies and practice in the Asian business sector - Zeyar Myo Aung U 1973-; Ordóñez de Pablos, Patricia 1975- (Advances in logistics, operations, and management science (ALOMS) book series, 2016)
"This book is a comprehensive reference source for theories and practices related to business integration in Asian countries"...